P270 Bile acid malabsorption incidence and diagnosis in clinical practice. (16th January 2018) - Gros, B; Mena, L; Benítez, J M; Carmona, E; Marín, S; Maza, F; Medina, R; García-Sánchez, V; Iglesias-Flores, E
Abstract: Background: Bile Acid Malabsorption (BAM) is a well-known disorder whose understanding is increasingly recognised. Proper diagnostic methods and treatments are emerging in the last decades leading to a bigger relevance in clinical practice, although nowadays it is still underdiagnosed. The diagnostic challenge behind diarrhoea symptom carries an important economic expense. 75SeHCAT test is the current gold standard in Europe for diagnosing BAM. BAM is classified into type 1: secondary to ileal resection or disease; type 2 idiopathic; type 3 secondary to various gastrointestinal diseases (cholecystectomy, vagotomy, celiac disease, etc.). The aim of this study was to investigate the frequency of BAM with 75SeHCAT scanning among patients suffering from chronic watery diarrhoea and to compare the incidence in Crohn's disease (CD) patients with non CD. Methods: We analysed retrospectively 81 patients with chronic diarrhoea, between August 2015 and October 2017. We included patients with inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), cholecystectomy, chronic pancreatitis among others. No patients had received treatment with bile acid sequestrants (Cholestyramine) before. We perform the test after the ingestion of a 75SeHCAT capsule (0.37 MBq) prior fasting the night before. Seven-day measurements were compared with 3 h activity to calculate the abdominal retention percentage. The interpretation of the retention results was ≥10% BA is consistent with a normal result. Mild BAM 7–10%, moderate 4–7% and severe <4% retention. Results: We studied 51 women and 30 men, mean age 46.3. 40 suffered from Crohn's disease (CD), 2 ulcerative colitis (UC), 4 ileal resection due to neoplasia, 11 cholecystectomies, 1 Meckel diverticulum, 1 primary sclerosing cholangitis (PSC), 1 appendectomy, 2 IBS-Diarrhoea, 1 chronic pancreatitis, 1 eosinophilic colitis, 17 diarrhoea with no diagnosis. After performing 75SeHCAT scan, 75.3% had abnormal values. 80.3% severe malabsorption, 11.5% moderate and 8.2% mild malabsorption. When considering the classification of BAM, 54.3% were type 1, 25.9% type 2 and 19.8% type 3. Regarding to patients with ileal disease o ileal resection, 95.5% presented BAM (type 1). 39 were CD patients, 84.6% presenting intestinal resection. The rest of patients of our cohort presented 42.9% type 2-BAM and 62.5%-type 3. Conclusions: A higher than expected incidence was found among the different groups. CD with chronic diarrhoea present high incidence of BAM when activity of their disease is discarded. According to BAM type 2 we found a higher number affected than those described in the literature. When studying diarrhoea as a symptom, BAM should be considered in the differential diagnosis.